Trade unionism and the Chartist movement, 1833-1910. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2012)
George Howell, (1833-1910) was a prominent and well connected member of the labour movement during the growth of trade unions and the Chartist movement's fight for male suffrage. During his time as an apprentice shoemaker he was introduced to radical publications like the Northern Star and Red Republican and subsequently became a member of the Chartist movement in 1848. He steadily gained a strong reputation in the rising labour movement and worked with figures like Karl Marx, Charles Bradlaugh, George Jacob Holyoake, E. S. Beesly, and Frederic Harrison. Howell became Secretary of the Reform League in 1865, and was also involved in the London Trades Council and Marx's International Workingmen's Association. He later became a Member of Parliament for North East Bethnal Green in 1885 as part of the Liberal-Labour movement. The collection contains a wealth of material from the many organisations and movements that Howell contributed to. This includes minutes, circulars, press cuttings, and reports from the International Workingmen's Association, the Reform League, and the Trade Union Congress. Additionally, there is also an abundance of correspondence between Howell and key figures within the 19th century labour movement, as well as Howell's intimate personal diaries and autobiographical material. The collection is also accompanied by a detailed guide written by Stefan Dickers.
Date range: 1833-1910.
Keywords: Howell, George, -- 1833-1910.; Working class -- Political activity -- Great Britain -- History -- 19th century; Radicalism -- Great Britain -- History -- 19th century; Great Britain -- Politics and government -- 1837-1901.